2010
DOI: 10.1007/s11694-010-9096-y
|View full text |Cite
|
Sign up to set email alerts
|

Discrimination of yerba mate (Ilex paraguayensis St. Hil.) samples according to their geographical origin by means of near infrared spectroscopy and multivariate analysis

Abstract: Near infrared reflectance (NIR) spectroscopy combined with multivariate data analysis was used to discriminate between the geographical origins of yerba mate (Ilex paraguayensis St. Hil.) samples. Samples were purchased from the local market and scanned in the NIR region (1100-2500 nm) in a monochromator instrument in reflectance. Principal component analysis (PCA), partial least squares discriminant analysis (PLS-DA) and linear discriminant analysis (LDA) were used to classify the samples based on their NIR s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 23 publications
1
8
0
2
Order By: Relevance
“…With respect to PLS-DA, Cozzolino et al (2010) analysed the entire NIR reflectance spectra of yerba mate and obtained results similar of those of the present study. As reported by Marcelo, Martins, Pozebon, Dressler, et al (2014), variable selection was necessary in order to improve the classification of yerba mate by PLS-DA and SVM-DA of the NIR reflectance spectra.…”
Section: Supervised Methodssupporting
confidence: 83%
See 2 more Smart Citations
“…With respect to PLS-DA, Cozzolino et al (2010) analysed the entire NIR reflectance spectra of yerba mate and obtained results similar of those of the present study. As reported by Marcelo, Martins, Pozebon, Dressler, et al (2014), variable selection was necessary in order to improve the classification of yerba mate by PLS-DA and SVM-DA of the NIR reflectance spectra.…”
Section: Supervised Methodssupporting
confidence: 83%
“…From an economic perspective, authenticity is essential to avoid unfair competition, because producers associate their brands with a given region in order to obtain market recognition, commercial advantages and better prices (Karoui & De Baerdemaeker 2007). Cozzolino et al (2010) identified yerba mate from Argentina and Uruguay by means of near-infrared spectroscopy (NIR) and multivariate analysis of the NIR spectra, whereas linear discriminant analysis (LDA) and partial least square discriminant analysis (PLS-DA) were used. Using a similar approach, Marcelo, Martins, Pozebon, Dressler, et al (2014) identified yerba mate from Argentina, Brazil, Uruguay and Paraguay.…”
Section: Please Scroll Down For Articlementioning
confidence: 99%
See 1 more Smart Citation
“…The first dataset refers to Yerba mate ( Ilex paraguariensis ), which has been cultivated and consumed in southern Latin America for centuries because of its medicinal properties . Previous works dealing with the problem of classifying yerba mate samples include Choi et al , who reported a successful discrimination between 11 Ilex species from different origins by means of multivariate analysis of their metabolite fingerprints obtained by 1H NMR, and Cozzolino et al , who applied PLS‐DA (Partial Least Squares – Discriminant Analysis) regression and LDA to discriminate between samples of yerba mate coming from three different countries. The application of the method proposed in this paper to 54 samples of yerba mate proceeding for four countries increased the classification accuracy average 36.75%, from 0.7156 to 0.9786, and retained average 3.54% of the original wavelengths.…”
Section: Introductionmentioning
confidence: 99%
“…Sendo assim, as distâncias são apresentadas comumente de forma relativa. 11 Para a erva mate, por exemplo, a HCA foi capaz de identificar o produto comercial por país de origem mediante o perfil de reflexão na região do infravermelho próximo (NIR) 12,13 e diferenciar as plantas da família Ilex através do perfil da composição das plantas obtido mediante espectrometria de ressonância magnética nuclear de hidrogênio (RMN de H 1 ). 14 A Análise por Componentes Principais (PCA) é a base fundamental da maioria dos métodos de tratamento multivariado de dados.…”
Section: Introductionunclassified